A new system for classifying threatened status - IUCN Species Survival Commission (Neotropical Primates, 1995)
The IUCN Species Survival Commission (SSC) of the World Conservation Union (IUCN) recently published the official text which provides information on, and the definitions for, the new threatened status categories adopted by IUCN at the 40th Meeting of the IUCN Council, Gland, Switzerland. The evaluation of the status of animal and plant species is one of the principal tasks of the SSC Specialist Group network, and for this reason we are publishing the text in its entirety.